Model incorporating the ITPA genotype identifies patients at high risk of anemia and treatment failure with pegylated‐interferon plus ribavirin therapy for chronic hepatitis C1. Issue 3 (7th January 2013) - Kurosaki, Masayuki; Tanaka, Yasuhito; Nishida, Nao; Sakamoto, Naoya; Enomoto, Nobuyuki; Matsuura, Kentaro; Asahina, Yasuhiro; Nakagawa, Mina; Watanabe, Mamoru; Sakamoto, Minoru; Maekawa, Shinya; Tokunaga, Katsushi; et al.
Abstract This study aimed to develop a model for predicting anemia using the inosine triphosphatase (ITPA) genotype and to evaluate its relationship with treatment outcome. Patients with genotype 1b chronic hepatitis C (n = 446) treated with peg‐interferon alpha and ribavirin (RBV) for 48 weeks were genotyped for the ITPA (rs1127354) and IL28B (rs8099917) genes. Data mining analysis generated a predictive model for anemia (hemoglobin (Hb) concentration <10 g/dl); the CC genotype of ITPA, baseline Hb <14.0 g/dl, and low creatinine clearance (CLcr) were predictors of anemia. The incidence of anemia was highest in patients with Hb <14.0 g/dl and CLcr <90 ml/min (76%), followed by Hb <14.0 g/dl and ITPA CC (57%). Patients with Hb ≥14.0 g/dl and ITPA AA/CA had the lowest incidence of anemia (17%). Patients with two predictors (high‐risk) had a higher incidence of anemia than the others (64% vs. 28%, P < 0.0001). At baseline, the IL28B genotype was a predictor of a sustained virological response [adjusted odds ratio 9.88 (95% confidence interval 5.01–19.48), P < 0.0001]. In patients who achieved an early virological response, the IL28B genotype was not associated with a sustained virological response, while a high risk of anemia was a significant negative predictor of a sustained virological response [0.47 (0.24–0.91), P = 0.026]. For high‐risk patients with an early virological response, giving >80% of the planned RBV dose increased sustained virological responses by 24%. In conclusion, a predictive model incorporating the ITPA genotype could identify patients with a high risk of anemia and reduced probability of sustained virological response. J. Med. Virol. 85:449–458, 2013. © 2013 Wiley Periodicals, Inc.